Functional Space Consisted by Continuous Functions on Topological Space - Yamazaki, Hiroshi; Miyajima, Keiichi; Shidama, Yasunari (Formalized Mathematics, 2021)
In this article, using the Mizar system [1], [2], first we give a definition of a functional space which is constructed from all continuous functions defined on a compact topological space [5]. We prove that this functional space is a Banach space [3]. Next, we give a definition of a function space which is constructed from all continuous functions with bounded support. We also prove that this function space is a normed space.